Comparison of Positive Law and Islamic Law In Recognition Outside Marriage Children's Legal Status - Siti Rabiah Rumadaul (Musamus Law Review, 2020)
Recognition of the legal status of children outside of marriage is regulated in Article 280 of the Civil Code and Islamic Law does not recognize the recognition of children outside of marriage which is regulated in Article 100 of the Compilation of Islamic Law, so that the legal consequences that arise later are different. A child outside of marriage is a child born to his parents without a legal marriage between the father and mother. Therefore, the child does not have the status or position in law as a legitimate child. This type of research conducted by the author is Empirical Juridical Research, namely research by studying, investigating and studying according to what has been determined by the applicable regulations and real facts that occur in the community with the aim to learn and find data and real events that actually happened, with use the legal approach and case approach. In the results of this research and discussion it is explained that in Positive Law a child outside of marriage can be ratified by a confession, whereas in Islamic Law there is no recognition. Recognition of children outside of marriage in Positive Law raises the result of the endorsement and the resulting relationship with the legal consequences. Whereas in Islamic Law the law of an out-of-wedlock child is not entitled to obtain lineage relationship, livelihood, inheritance rights and others from his biological father because it only has a lineage relationship with his mother and his mother's family, but if the biological father wants to give part of his property, this can be done through a will. Related to the difference between the recognition of Positive Law and Islamic Law, it is considered necessary to pay attention, because of the importance of recognition of children outside of marriage, which results in civil rights in the future. Then later the child outside of marriage also gets the distribution of inheritance (inheritance), guardianship rights and other rights. The government through legislation also needs to pay attention to the management of the inheritance (inheritance) of children outside of marriage so that it becomes an absolute right for children outside of marriage in the future.